PEMANFAATAN LIMBAH KULIT KAKAO SEBAGAI BAHAN DASAR PEMBUATAN PUPUK ORGANIK CAIR (POC) UNTUK BUDIDAYA TANAMAN HOLTIKULTURA DI LAHAN PEKARANGAN RUMAH DESA GENGGELANG, KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Thabrani, Rijal; Amalia, Yunda Fitri Rizky; Zuhraini, Zuhraini; Pandini, Intan; Candri, Dining Aidil (Universitas Mataram, 2023)
Real Work Lecture (KKN) is a form of community service activity carried out by tertiary institutions. In the KKN activities carried out in Genggelang Village, Gangga District, North Lombok Regency, groups of students and lecturers at the University of Mataram carried out various activities with the main goal of developing the village's agricultural potential. The purpose of implementing this KKN activity is to answer various problems related to agriculture and help solve social issues. The problem that has been identified is the large amount of plantation waste that is not utilized which can cause environmental pollution. In an effort to overcome the problem of plantation waste that is not utilized optimally. The efforts made by the Mataram University Community Service students are to process the waste into organic fertilizer which can be reused by the farmers there as a support for holicultural plants in the residents' yards. So that the holicultural plants in the residents' yards can thrive in the presence of this organic fertilizer. With the activity of making fertilizer from plantation waste, the community can increase the selling value of community plantation products where, in addition to being able to sell the main plantation products, the community can sell waste that has been processed into fertilizer so that garden products can be utilized as much as possible.